Social and Academic Segregation in the Education Systems of the New EU Member States - Stumbrienė, Dovilė; Jakaitienė, Audronė; Želvys, Rimantas (Socialinė teorija, empirija, politika ir praktika, 2019)
This article presents a comparative analysis of the educational systems of EU countries, exploring them from a socioeconomic perspective with a special focus on new EU member states. The research question was whether post-socialist countries, in terms of social and academic segregation, are moving toward a separate educational “regime,” or whether they are currently approaching either the Scandinavian, Continental, Anglo-Saxon, or Mediterranean model. Segregation was analyzed according to performance scores in science and economics, social and cultural status, and hierarchical regression was employed in analyzing PISA 2015 data. Results indicate that post-socialist EU member states, in terms of academic and social segregation, do not form a separate “educational regime.”